Pengaruh Komunikasi Interpersonal Guru, Student Engagement dan Efikasi Diri terhadap School Well-Being Siswa SMPN 1 Semanu Kabupaten Gunungkidul - Kuswoyo Kuswoyo; Nurul Hidayah; Ahmad Muhammad Diponegoro (Jurnal Syntax Transformation, 2021)
This study aims to 1) test the influence between teacher interpersonal communication, student engagement and self-efficacy on school well-being. 2) test the influence of teacher interpersonal communication on school well-being. 3) test the influence of student engagement on school well-being. 4) test the effect of self-efficacy on well-being schools. The population is students of SMP Negeri 1 Semanu Gunungkidul Regency. The research sample was grade VI A, VIII C and IX A students who numbered 95 students. Sampling techniques use cluster random sampling. The data collection method uses a research instrument consisting of four research scales, namely the school well-being scale, the teacher interpersonal communication scale, the student engagement scale and the self-efficacy scale. The data analysis technique used is multiple regression analysis with the help of SPSS 25.0. The results of this study are 1) there is a very significant influence between teacher interpersonal communication, student engagement and self-efficacy towards school well-being, with a value of significance = 0.000 < (0.01), a value of F of 35,880 and a value of R = 0.542. 2) there is a positive and very significant influence between teacher interpersonal communication towards school well-being with significance value = 0.000 < 0.01 and value t = 3.777. 3) there is a positive and significant influence between student engagement towards school well-being with significance value = 0.027 < 0.05 and value t = 2.246. 4) there is a positive and very significant influence between students' self-efficacy towards well-being school with significance value = 0.000 < 0.01 and t value = 4.973